Improving Students' Understanding of Arabic Grammar (Nahwu) Through The Think-Pair-Share Model - Farahmahsa Aziarida; Aina Salsabila; J Nurhawani (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Arabic grammar (Nahwu) is an essential component, yet students often find it difficult due to monotonous teaching methods. This study was motivated by students’ low level of understanding and interest in Nahwu rules at school. This study aims to evaluate the effectiveness of the Think-Pair-Share model in improving eighth-grade students’ understanding of nominal and verbal phrases at MTsN 1 Aceh Utara. The method used is quantitative research with a quasi-experimental design of the non-equivalent control group type. The study population consisted of 235 students divided into eight classes, while the sample of 42 students was selected purposively, divided into an experimental class (n=21) and a control class (n=21). Data were collected through pre- and post-tests and analyzed using the Wilcoxon and Mann-Whitney tests in SPSS 25. The results showed a significant improvement in the experimental class with a post-test mean score of 74.23, outperforming the control class, which scored only 48.76. The N-Gain score for the experimental class reached 64.13% (classified as moderately effective), while the control class scored only 31.37%. The Mann-Whitney test yielded a significance value of 0.000 < 0.05. Thus, the TPS Model has proven effective in improving students’ understanding of Nahwu by encouraging them to construct their thinking independently and collaboratively. This helps students gain a deeper understanding of sentence structure than expository methods do.